Pengaruh Metode Pembelajaran Show and Tell Berbantuan Media Gambar Seri terhadap Kemampuan Bercerita Siswa Kelas 4 Sekolah Dasar - Rosyada, Irfani Amrina; Azmy, Bahauddin (ARZUSIN, 2025)
This research aims to determine the effect of the show and tell learning method assisted by picture series media on the storytelling ability of 4th grade students at SD Ana Maritim Surabaya. This research is a quantitative experimental research. The research design used is Pre-Experimental Design (nondesign) One-Group Pre-test Post-test Design. The pretest was carried out to measure students' abilities before the learning methods and media were applied, and the posttest was carried out to measure students' abilities after the learning methods and media were applied. The place where this research took place was at SD Ana Maritim Surabaya. The subjects in this research were 4th grade students at SD Ana Matitim Surabaya for the 2024/2025 academic year with a total of 25 students. The data collection technique used is a test, and the instruments used are pretest and posttest. The results of this research are proven by the value of the T Test results which shows the pretest and posttest t count is 9.538 and the t table is 2.060, which means 9.538 > 2.060 and sig 0.000 < 0.05 so it can be stated that the hypothesis is accepted based on the assumptions of the previous hypothesis.